Entrepreneur - Ning Purnama Sariati (Istithmar: Jurnal Studi Ekonomi Syariah, 2017)
The true life story of Prophet Mohamad as a trader is wonderful on this earth. No ones could follow him well. Habitual action of prophet Mohammad is very meaningful on whole life. Not only on the religion but also business. He got success by honesty, trusting, beliefing on Allah and makes good society empowerment. So, his life bring happiness and peace (rahmatan lil alaamiiiiin). In other hands, human being are not conduct their life like Prophet Mohamad. For example, business aspect. We have been know market distortion was happened in society. Kinds of market distorsion are taghrir, tadlis, lying, diminution of scales, and else. This research aims to: describe the habitual action of the moslem hawkers based on character of Prophet Mohamad SAW as a trader. This research is categorized into descriptive research type with qualitative method. The respondent are moslem hawkers as member of “Paguyuban PKL Bina Mandiri Kota Kediri. Data collection was conducted through in-depth interview and observation. The obtained data was analyzed by qualitative analysis procedurs. The result shows that: habitual action of the moslem hawkers has been follow the character of Prophet Mohammad SAW as a trader. In the implementation of moslems hawkers community Bina Mandiri Kota Kediri are moral self quality, moral business quality, moral social quality and positive progress empowerment. They are aware on business is praying to Allah,not only profit oriented.